Reduced economic burden of AIDS-defining illnesses associated with adherence to antiretroviral therapy. (February 2020) - Toh, Han-Siong; Yang, Chun-Ting; Yang, Kai-Li; Ku, Han-Chang; Liao, Chia-Te; Kuo, Shihchen; Tang, Hung-Jen; Ko, Wen-Chien; Ou, Huang-Tz; Ko, Nai-Ying
Highlights: Improved adherence to ART increased annual baseline costs in HIV-infected patients. Having ADIs significantly increased annual costs up to 99% (i.e., cryptococcosis). ADIs occurred less frequently in years with improved adherence to ART. Economic burden of ADIs was attenuated in years with improved adherence to ART. Abstract: Objectives: We assessed the economic burden of AIDS-defining illnesses (ADIs), which was further stratified by adherence to antiretroviral therapy (ART). Methods and materials: A nationwide longitudinal cohort of 18, 234 incident cases with HIV followed for 11 years was utilized. Adherence to ART was measured by medication possession ratio (MPR). Generalized estimating equations modeling was used to estimate the cost impact of ADIs. Results: Having opportunistic infections increased the annual cost by 9% (varicella-zoster virus infection) to 98% (cytomegalovirus disease), while the annual costs increased by 26% (Kaposi's sarcoma) to 95% (non-Hodgkin's lymphoma) in the year when AIDS-related cancer occurred. ADIs occurred more frequently in the years with low adherence for ART compared to the high-adherence years (e.g., 0.1 ≤ MPR < 0.8 vs. MPR ≥ 0.8, event rate of cytomegalovirus disease 4.03% vs. 0.51%). The annual baseline costs in the years with MPR < 0.1, 0.1 ≤ MPR < 0.8, and MPR ≥ 0.8 were 250, 4, 752, and 8, 990 (in 2018 USD), respectively. The economic impact of ADIs in the years with low adherence (MPR < 0.1) was larger than that in the high-adherence years (MPR ≥ 0.8) (e.g., MPR < 0.1 vs. MPR ≥ 0.8, annual cost increased by 244% vs. 9% when candidiasis occurred). Conclusions: Adherence to ART may increase the baseline medical costs but mitigate the incidence and economic burden of ADIs.